Electrical and Optical Properties of Nickel-Oxide Films for Efficient Perovskite Solar Cells - Hossain M.I. (John Wiley and Sons Inc., 2023)
Conversion efficiency; Finite difference time domain method; Nickel oxide; Optical losses; Oxide films; Perovskite; Perovskite solar cells; Physical vapor deposition; Refractive index; Thin films; Time domain analysis; Complex refractive index; Crystalline properties; Electrical and optical properties; Electrical characteristic; Electron beam-physical vapor deposition; Finite difference time domain simulations; Finite element method simulation; Solar cell structures; Optical films